1347. Improved Antibiotic Prescribing Practices for Respiratory Infections Through Use of Computerized Order Sets and Educational Sessions in Pediatric Clinics. (31st December 2020) - Zahlanie, Yorgo; Mang, Norman; Lin, Kevin; Hynan, Linda S; Prokesch, Bonnie C
Abstract: Background: The literature about comprehensive outpatient antimicrobial stewardship programs remains sparse. However, computerized clinical decision support systems (CDSSs) have shown promising effectiveness in improving outpatient antibiotic prescribing. Methods: We developed an intervention in the form of EPIC order sets comprised of outpatient treatment pathways for 3 pediatric bacterial acute respiratory infections or ARIs (otitis media, community-acquired pneumonia, and streptococcal pharyngitis) coupled with educational sessions. Two study periods were included, and 4 pediatric clinics were randomized into intervention and control arms. Education was provided to the 2 intervention clinics between the study periods, and EPIC order sets became available to these 2 clinics at the beginning of the post-intervention period. The primary endpoint was the rate of first-line antibiotic prescribing, and the secondary endpoints included antibiotic duration and antibiotic prescription modification within 14 days. Results: A total of 2690 antibiotic prescriptions were written for bacterial ARIs. At pre-intervention, there was no difference between the study arms in terms of first-line antibiotic prescribing (74.9% vs. 77.7%, P =0.211) and antibiotic duration (9.69 ±0.96 days vs. 9.63 ±1.07 days, P >0.999). Following the intervention, the intervention clinics had higher rate of first-line antibiotic prescribing (83.1% vs. 77.7%, P =0.024) and shorter antibiotic duration (9.28 ±1.56 days vs. 9.79 ±0.75 days, P < 0.001) compared to the control clinics. The rate of modified antibiotics was small in all clinics (1.1-1.6%) and not different at pre-intervention ( P =0.852) and post-intervention ( P =0.552). Analysis of categorical variables Analysis of continuous variables Distribution of the antibiotic prescriptions among the 3 bacterial acute respiratory infections Conclusion: A computerized CDSS involving treatment pathways in the form of order sets coupled with educational sessions was associated with a higher rate of first-line antibiotic prescribing and shorter antibiotic duration for the outpatient treatment of bacterial ARIs. More studies are needed in order to assess the utility of multimodal approaches in pediatric outpatient antimicrobial stewardship. Disclosures: All Authors : No reported disclosures